Assessing The Effects Of Black Pepper (Piper Nigrum) Aromatherapy On Cigarette Consumption: A Double-Blind Randomized Controlled Trial - Luh Nyoman Alit Aryani,; Ni Made Wartini,; I Putu Belly Sutrisna,; Gusti Ayu Arya Prima Dewi,; I Komang Ana Mahardika,; Ayu Indra Rumpa,; G. A. Ade Cahayani Saraswati,; Komang Wiswa Mitra Kenwa, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The global use of tobacco is becoming increasingly concerning. Nicotine addiction management now explores innovative options like aromatherapy. Black pepper (Piper nigrum) essential oil shows potential as an aid in smoking cessation. Objective: This study aimed to evaluate the effects of black pepper aromatherapy on cigarette consumption and nicotine dependence. Methods: Conducted as a double-blind randomized clinical trial at the Class II A Kerobokan Correctional Institution Clinic from July to September 2024, the study included smokers aged 12 years and older. Participants were randomly assigned to receive aromatherapy with either black pepper essential oil or plain water, with 30 participants per group. Weekly cigarette usage was self-reported, and nicotine dependence was measured using the Fagerström Test for Nicotine Dependence (FTND). SPSS version 25.0 was used for data analysis. Results: At baseline, both groups were comparable in age, FTND scores, and cigarette consumption. Over four weeks, the black pepper group showed a significantly greater reduction in daily cigarette consumption, particularly in Week 4 (p = 0.002), compared to controls. Repeated measures ANOVA indicated a significant decrease in the black pepper group (F = 80.022, p < 0.001), with progressive reductions each week. FTND scores also significantly declined, with greater reductions in the black pepper group (mean difference = -1.300, p = 0.004). No serious adverse effects were reported. Conclusion: Black pepper aromatherapy may aid in reducing cigarette use and nicotine dependence, supporting its potential as an adjunct in smoking cessation.